THE RESULTS OF THE STUDY OF WINTER BARLEY VARIETIES IN THE ROSTOV REGION - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; A. A. Makarenko (Зерновое хозяйство России)
One of the most important trends of the stable production of winter barley is the introduction of new varieties of into production [4]. The reasonable selection of the initial material and its further introduction into the breeding program gives an opportunity to solve the problem successfully. Identification, selection and development of the initial material are the main elements of the successful breeding of crops. Thus, the purpose of our researches was to study the main economic-valuable traits of winter barley varieties in the Rostovregion and to identify a valuable initial material in the variety-testing for their use in the development of new varieties. The experiments were carried out on the fields of the scientific crop rotation of the department of barley breeding and seed-growing of FSBSI ARRIGC after I.G. Kalinenko in the years of 2013-2015. The subjects of the study were 18 varieties of winter barley with different ecologic-geographic origin. The varieties with the combination of economic-valuable traits and properties were identified. The varieties ‘Zhiguli’, ‘Timofey’ (FSBSI ARRIGC after I.G. Kalinenko) and ‘Fedor’ (FSBSI KRIA after P.P. Lukiyanenko) were found to combine great number of grains pre head and tolerance to leaf diseases. The varieties ‘Vivat’ (FSBSI ARRIGC after I.G. Kalinenko) and ‘Samson’ (FSBSI KRIA after P.P. Lukiyanenko) were identified as the most productive varieties, resistant to lodging, powdery mildew and net blotch (Helminthosporium teres). The variety ‘Broinskayly’ (France) showed a good combination of coarse grain and high resistance to leaf diseases.